2014
DOI: 10.1016/j.radonc.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Second primary cancers after radiation for prostate cancer: A systematic review of the clinical data and impact of treatment technique

Abstract: The development of a radiation induced second primary cancer (SPC) is one the most serious long term consequences of successful cancer treatment. This review aims to evaluate SPC in prostate cancer (PCa) patients treated with radiotherapy, and assess whether radiation technique influences SPC. A systematic review of the literature was performed to identify studies examining SPC in irradiated PCa patients. This identified 19 registry publications, 21 institutional series and 7 other studies. There is marked het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 57 publications
(113 reference statements)
4
83
0
2
Order By: Relevance
“…13 Historically, this has been defined as five years. 13 21-23 There were differences in the use and application of the length of the lag period from the time of treatment to diagnosis of secondary cancer among included studies.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…13 Historically, this has been defined as five years. 13 21-23 There were differences in the use and application of the length of the lag period from the time of treatment to diagnosis of secondary cancer among included studies.…”
Section: Outcomementioning
confidence: 99%
“…9 10 One previous review concluded a negligible risk of secondary malignancies after radiotherapy, 11 whereas other reviews concluded that this is an important risk for both patients and physicians to consider. [12][13][14] A previous meta-analysis lacked data from several important recent publications. 15 While direct radiation carcinogenesis has long been accepted, 16 there is evidence that irradiation of the prostate might contribute to carcinogenesis outside the irradiated area through radiation scatter and radiation induced genetic alterations without direct exposure because of increased reactive oxygen species [17][18][19] and…”
Section: Introductionmentioning
confidence: 99%
“…Radiation induced second cancers (RISC) are rare but relevant late effects of radiation therapy (RT) [1, 2]. In principle most of the knowledge regarding RISC is derived from epidemiological data of atomic bomb survivors, nuclear accidents and database analyses [3].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent malignancies are an uncommon but serious and debilitating consequence of radiation therapy for the treatment of cancer (1). Among men who elect treatment for prostate cancer, nearly two-thirds of those who are older than 65 years of age receive some form of radiation therapy (RT), and one-third undergo surgery (2).…”
Section: Introductionmentioning
confidence: 99%